Kajian komplian penggunaan alat perlindungan diri pekerja kilang keluli, Terengganu - Sirajuddin Hashim,; Emilia Zainal Abidiin,; Noor Hassim Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
A cross-sectional study was conducted to determine the prevalence of compliance on personal protective equipments among 240 workers in three different divisions involving steel production division, direct reduction iron division and the mechanical division at a steel factory in Terengganu. A series of guided questionnaire were issued to all the workers in the three divisions to measure the prevalence of compliance to five types of personal protective equipments which consist of safety helmet, mask, eye-protective gear, ear-plugs and safety boots. The prevalence compliance to safety helmet, mask, eye protection gear; ear-plugs and safety boots was 67.1%, 35.3%, 32.0%, 41.1% and 99.2% respectively. There was a significant relationship (p<0.05) between the compliance to safety helmets with type of work being done and for ear-plugs, relationship with compliance were significantly associated with type of work done, duration of use and fit-testing. Findings of this study also supports the hypothesis that compliance was associated with unimpeded movement, unaffected productivity and unhindered work task (p<0.05). Age and tenure in service have no significant relationship with compliance. Knowledge on safety and health issues were shown to relate to compliance with safety helmets (p<0.01). It is suggested that the management embark on risk assessment programs to be able to explicitly determine the suitability of personal protective equipment being used in regards to type of work, specifications and comfort of workers.Management should also take a firm stand by developing a policy that supports compliance of personal protective equipments.